BRAF V600E Immunoexpression in Papillary Thyroid Carcinoma and Its Association with Prognostic Factors and Histopathologic Variant - Kristiani, Erna; SR Hardjolukito, Endang; S Harahap, Agnes; Makes, Benyamin (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Aim: to provide additional information regarding the clinicopathological characteristics of Papillary Thyroid Carcinoma (PTC). Methods: Fifty patient with PTC were reviewed to determine prognostic factors such as age, gender, size of tumor and histologic variant. BRAF V600E mutation was detected by immunohistochemical staining and assessed with H score. Result: BRAF V600E mutations were detected in 17 (34%) cases. There were seven cases with extrathyroidal extension (ETE) p 0,04, 11 cases with lymph node metastasis (LNM) p < 0,001, and 8 cases with tall cell variant p 0,047.The cases with positive BRAF V600E mutation had mean age of 44.71 years, and the size of the tumor between 0.1-4cm. Six cases of them are male and 11 female.Conclusion: There were significant relationships between BRAF V600E mutation with ETE, LNM, and tall cell variant. There was no significant relationship between BRAF V600E mutation, either with age, gender, or size of the tumor. BRAF V600E immunohistochemical examination can be performed as additional investigation for PTC patients.